1999
DOI: 10.1128/iai.67.9.4557-4562.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Variable Sequence in the P1 Cytadhesin Gene of Mycoplasma pneumoniae : Evidence for the Generation of Antigenic Variation by DNA Recombination between Repetitive Sequences

Abstract: A Mycoplasma pneumoniae cytadhesin P1 gene with novel nucleotide sequence variation has been identified. Four clinical strains of M. pneumoniae were found to carry this type of P1 gene. This new P1 gene is similar to the known group II P1 genes but possesses novel sequence variation of approximately 300 bp in the RepMP2/3 region. The position of the new variable region is distant from the previously reported variable regions known to differ between group I and II P1 genes. Two sequences closely homologous to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 33 publications
(45 reference statements)
0
42
0
1
Order By: Relevance
“…Since the first description in 1999 (Kenri et al, 1999), variants of type 2 have been reported in different regions. It is believed that variants are generated by homologous recombination between repetitive regions of the p1 gene and similar regions that are distributed across the bacterial genome (Kenri et al, 1999;Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first description in 1999 (Kenri et al, 1999), variants of type 2 have been reported in different regions. It is believed that variants are generated by homologous recombination between repetitive regions of the p1 gene and similar regions that are distributed across the bacterial genome (Kenri et al, 1999;Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description in 1999 (Kenri et al, 1999), variants of type 2 have been reported in different regions. It is believed that variants are generated by homologous recombination between repetitive regions of the p1 gene and similar regions that are distributed across the bacterial genome (Kenri et al, 1999;Zhao et al, 2011). The present results differ from those obtained by Martínez et al in Chile, who observed the circulation of type 1 (78.3%) and type 2 (21.7%) strains of M. pneumoniae, and a small proportion (7.1%) of variants of type 2 during the 1-year study period (Martínez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two subtypes of M. pneumoniae most frequently isolated from clinical specimens differ to some extent in the amino acid and nucleotide sequences of P1 and its coding gene (Su et al, 1990), though numerous further variants have been identified in recent years (Kenri et al, 1999;Dorigo-Zetsma et al, 2000Dumke et al, 2004;Pereyre et al, 2007). Although it has not been demonstrated experimentally, the source of these variant sequences is likely to be degenerate repeats of regions of the P1-coding gene present throughout the M. pneumoniae genome (Kenri et al, 1999); recent evidence in the related organism Mycoplasma genitalium supports a model in which these regions interchange with complementary regions, generating diversity in the P1 sequence (Iverson-Cabral et al, 2007;Ma et al, 2007). A recent report from Japan (Kenri et al, 2008) analyzed clinical isolates of M. pneumoniae collected over a several year period to characterize the P1 gene DNA and determined that the prevalent subtype of M. pneumoniae between 1995 and 2001 was group II but that group I strains became more prevalent between 2002 and 2005.…”
Section: Molecular Basis For Cytadherence and Production Of Diseasementioning
confidence: 99%
“…For example, in the closely related Mycoplasma pneumoniae and M. genitalium genomes, many parts of the gene coding for the major adhesin, P1 in the former and MgPa in the latter, are repeated (Peterson et al, 1995;Himmelreich et al, 1996). Recombination between these repeats leads to the generation of new variants of the adhesins (Kenri et al, 1999;Iverson-Cabral et al, 2006, 2007. Although initial reports suggested that this variation was linked to antigen variation, the analysis of genome data in the light of experimental analysis of patients' antibodies and the low rate of sequence variation suggests that the variations proceeds for other reasons, for example to vary niche tropism (Rocha & Blanchard, 2002).…”
Section: Repeats As Evolutionary Reservoirsmentioning
confidence: 99%